10.1016/s1541-9800(05)70792-4 (CrossRef Listing of Deleted DOIs, 2000)
Aims This study aimed to investigate the incidence of low-dose quetiapine initiation and associated factors in adults newly diagnosed with depression in primary care. Methods We obtained medication dispensing records, primary and secondary care diagnoses and employment status for antipsychotic-naïve individuals aged 16-65 newly diagnosed with depression in primary healthcare from several national Finnish registers in 2016-2022. We then calculated the incidence of low-dose (≤50 mg) quetiapine initiation from 2 years before to 2 years after the depression diagnosis. Modified Poisson regression models derived adjusted risk ratios (aRRs) and 95% confidence intervals (CIs), assessing the association between covariates and low-dose quetiapine initiation. Results Of the 189 115 individuals with depression, 13.4% (25 373) initiated low-dose. The incidence of low-dose quetiapine peaked in the first 30 days following the depression diagnosis, constituting 14.8% of all initiations. Initiation had the strongest association with younger age (16-24 vs. 55-65 years: aRR 1.87, 95%CI 1.80-1.96) and psychiatric comorbidities, especially alcohol use disorder (1.44, 1.39-1.50) and other substance use disorders (1.27, 1.19-1.36). Ischaemic heart diseases had a positive association (1.13, 1.04-1.22), while hyperlipidaemia had a negative association (0.91, 0.86-0.97); other cardiometabolic conditions had no significant associations. Among other medications assessed, SSRI and hypnotic antidepressant use had the strongest associations with low-dose quetiapine initiation (1.81, 1.77-1.86 and 1.81, 1.77-1.85, respectively). Conclusions Low-dose quetiapine initiation is common among adults newly diagnosed with depression in primary care. The benefits of this practice should be weighed against cardiometabolic and other adverse effects.